A Simple Synthesis of Densely Substituted Benzofurans by Domino Reaction of 2-Hydroxybenzyl Alcohols with 2-Substituted Furans - Makarov, Anton S.; Kekhvaeva, Anna E.; Chalikidi, Petrakis N.; Abaev, Vladimir T.; Trushkov, Igor V.; Uchuskin, Maxim G. (Synthesis, 2019)
The Brönsted acid-catalyzed cascade synthesis of densely substituted benzofurans from easily available salicyl alcohols and biomass-derived furans has been developed. The disclosed sequence includes the intermediate formation of 2-(2-hydroxybenzyl)furans that quickly rearrange into functionalized benzofurans. The established protocol was applied for the total synthesis of sugikurojinol B.
Keywords: furan; benzofuran; rearrangement; sugikurojinol B